The Emerald Tutu: Floating Vegetated Canopies for Coastal Wave Attenuation - Hopkins, Julia; Lutsko, Nicholas; Cira, Gabriel; Wise, Louiza; Tegeler, Jena (Frontiers in Built Environment, 2022)
Nature-based solutions (NBS) have been broadly defined in coastal resilience as the restoration of natural environments or as civil infrastructure with natural elements, with examples ranging from marsh restoration and new oyster beds to artificial reefs and living shorelines. The multiplicity of NBS types makes it difficult to quantify and model their effectiveness as a whole in coastal flood reduction and environmental co-benefits. Specific types of NBS operate under a variety of physical and ecological regimes: oyster beds care about the benthic environment and can be modeled as bed roughness elements, while living shorelines are a combination of emergent/submerged vegetation elements located in the dynamic swash zone. As such, NBS cannot be investigated as a monolith and their evaluation will be intervention-specific. Here, we present the evaluation of an engineered NBS called the Emerald Tutu, a series of interlinked vegetated mats which leverage known physical and ecological properties of marsh environments and combine them in networked formats for rapid deployment around shoreline environments. The Tutu takes inspiration from marsh canopies, but aims to transport the physical protection of these canopies to urban areas using the wave attenuation properties of floating vegetation elements and network effects. Prototype Tutu units were deployed in the OH Hinsdale Wave Lab at Oregon State University in Summer 2021 to test the physical efficacy of the mat networks. The results show the effect of network arrangement, mat canopy size, and Tutu unit density on wave attenuation. We show how these results can be used to design the Tutu for a variety of coastal environments, and discuss the impact of submerged vegetation dynamics on Tutu effectiveness and what research gaps remain for the implementation of these kinds of engineered NBS.